ALK-positive inflammatory myofibroblastic tumor in the pelvis of a child: a case report and literature review - Yang, Lei; Yan, Zhiheng (Frontiers in Oncology, 2026)
Inflammatory myofibroblastic tumor (IMT) is a rare neoplasm that primarily affects children and young adults. While typically found in the lungs, liver, and gastrointestinal tract, pelvic involvement is recognized but occurs less frequently than intra-abdominal IMT, particularly in pediatric patients. Here we report a case of a 2-year-old boy who presented with a brief history of vomiting and decreased appetite. Imaging revealed a cystic-solid mass in the pelvis with progressive enhancement of the solid component, leading to suspicion of a vascular soft tissue neoplasm. Surgical exploration identified a free-floating mass within the abdominal cavity supported by a long vascular pedicle originating from the splenic hilum, an atypical anatomical finding that added complexity to preoperative diagnosis. Complete surgical resection was performed, and postoperative examination was conducted. Histopathological analysis confirmed IMT, and fluorescence in situ hybridization (FISH) detected ALK gene rearrangement, which supported diagnostic confirmation of IMT in this case rather than guiding therapeutic intervention. The patient recovered uneventfully following surgery, with no evidence of recurrence during follow-up. This case supports considering IMT in pediatric pelvic masses and reinforces that complete surgical resection remains the primary treatment. Although ALK gene rearrangement was not associated with therapeutic intervention in the present case, its identification remains diagnostically relevant and may provide important insights into management decisions in selected clinical scenarios, such as recurrence or unresectable disease.